Step-by-step explanation:
4+6+5=15
15-1=14
2/14
1/7
This is similar to the other question you posted. Follow the same steps as before.
First find g(41).
g(41) = sqrt{x - 5}
g(41) = sqrt{41 - 5}
g(41) = sqrt{36}
g(41) = 6
We now find f(6).
f(6) = -7(6) + 1
f(6) = -42 + 1
f(6) = -41
Answer:
(fºg)(41) = -41
Did you follow?
Answer:
The answer is 66.
Step-by-step explanation:
Subtract the two distances, and the answer is 266. Have a great day!
Answer:
D
Step-by-step explanation:
This function resembles that of the absolute value function, never going into the negative y values. Hope this helps!